Comparative Effects of Soil and Foliar Iron Application on Nutrient Dynamics in Green Gram - Adarsh Pandey; Karmnath Kumar; Shakti Om Pathak; Nilotpal Das; Atin Kumar; Sharad Sachan (Universitas Panji Sakti, 2026)
Iron deficiency is a common limitation in alkaline soils, restricting nutrient uptake and yield in pulse crops such as green gram (Vigna radiata L.). To compare various iron fertilization regimes and their effects on soil properties, nutrient dynamics, and nutrient uptake in green gram, a field experiment was conducted from March to July 2024 at SGT University, Gurugram, Haryana. The experimental design was a randomized block trial with three replicates because the experiment comprised seven treatments, including the recommended dose of fertilizers (RDF: 20:40:40 kg N: P₂O: K₂O ha-1) and soil and foliar applications of FeSO4. It was found that foliar application of FeSO4 significantly enhanced soil fertility and plant nutrient status compared to soil application. The highest soil organic carbon was recorded at 30 and 45 DAS with the RDF + foliar spray of 0.6% FeSO4 (0.41% and 0.40%, respectively), an increase of about 32-35% compared with the control (0.31-0.30%). Likewise, the available nitrogen content increased by 189.12 kg ha-1 to 225.08 kg ha-1 (about 19 percent improvement) under the same treatment. Nutrient levels in plant tissues also increased significantly, and nitrogen content in the straw and grain improved by 40-120 percent and 1.82-3.38 percent, respectively, compared to the control. The experiment shows that foliar iron application is more effective than soil-applied iron in improving nutrient status and plant uptake in alkaline soil. The originality of the study lies in its comparison of soil under staged foliar iron fertilization and its effects on the dynamics of soil nutrients, micronutrient availability, and nutrient use efficiency in the growth of green grass on alkaline soils.